Methodology for estimating the prospective CO2 storage resource of residual oil zones at the national and regional scale. (May 2020) - Sanguinito, Sean; Singh, Harpreet; Myshakin, Evgeniy M.; Goodman, Angela L.; Dilmore, Robert M.; Grant, Timothy C.; Morgan, David; Bromhal, Grant; Warwick, Peter D.; Brennan, Sean T.; Freeman, Philip A.; Karacan, C. Özgen; et al.
Highlights: Methodology for carbon dioxide storage resource estimation in residual oil zones. National and regional scale prospective CO2 resource estimation. CO2 storage in residual oil zones will predominately take place in the free phase. Abstract: Residual oil zones (ROZs) are increasingly gaining interest as potential reservoirs for carbon dioxide (CO2 ) storage. Here, we present a national- and regional-scale methodology for estimating prospective CO2 storage resources in residual oil zones. This methodology uses a volumetric equation that accounts for CO2 storage as a free phase in pore space and as a dissolved phase in oil and does not assume any oil production associated with CO2 storage. Reservoir modeling and the CO2 -SCREEN tool are used to demonstrate that CO2 storage in residual oil zones will predominantly take place in the free phase (approximately 92–97%) with some storage as dissolution in oil (approximately 3–8 %). Based on this preliminary demonstration, the CO2 storage efficiency for ROZs using this national- and regional-scale method ranges from 0.61 to 7.1 %. This range indicates ROZs have a similar efficiency potential for storing CO2 as deep saline formations (0.51–5.4 %).